Black thorn, white rose - Datlow, Ellen; Windling, Terri (New York : Avon Books, 1994)
Collection of stories remolding childhood fairy tales into darker, sexier stories for grown-ups.
Words like pale stones / Nancy Kress -- Stronger than time / Patricia C. Wrede -- Somnus's fair maid / Ann Downer -- The frog king, or Iron Henry / Daniel Quinn -- Near-beauty / M.E. Beckett -- Ogre / Michael Kandel -- Can't catch me / Michael Cadnum -- Journeybread recipe / Lawrence Schimel -- The brown bear of Norway / Isabel Cole -- The goose girl / Tim Wynne-Jones -- Tattercoats / Midori Snyder -- Granny Rumple / Jane Yolen -- The sawing boys / Howard Waldrop -- Godson / Roger Zelazny -- Ashputtle / Peter Straub -- Silver and gold / Ellen Steiber -- Sweet bruising skin / Storm Constantine -- The black swan / Susan Wade.
"AvoNova fantasy"--Spine.
Includes bibliographical references (p. 382-386).
Publisher's Weekly.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Fiction.
Adult
Keywords: Fairy tales -- Adaptations; Fantastic fiction, American; Fairy tales; Short stories; Fantastic fiction